2015
DOI: 10.1097/mcg.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the Management of Ulcerative Colitis

Abstract: Rapid progress has been made to understand the pathophysiology of inflammatory bowel diseases and to identify new treatments. Interaction of the gut microbiota on the host inflammatory response has suggested that alternative therapies, such as probiotics, might have a complementary role in treating and preventing disease flares. Multiple probiotics and their formulations have been studied for both the induction and maintenance of remission of ulcerative colitis (UC); however, mainly Escherichia coli Nissle 191… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…Alterations in microbiota composition or aberrant responses to luminal bacteria or dietary components can result in increased intestinal permeability, which may lead to the development of such pathologies. In this context, many studies have been conducted to investigate the therapeutic potential of certain commensal and probiotic strains to ameliorate inflammatory bowel diseases in clinical trials (reviewed by Chibbar and Dieleman, 2015; Wasilewski et al, 2015) or in animal models of colitis (Ewaschuk et al, 2008; Arribas et al, 2009; Shen et al, 2012; Kang et al, 2013; Martin et al, 2014; Souza et al, 2016). In mice colitis models, beneficial bacteria reduce inflammatory cytokines, normalize gut permeability, and reinforce the epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in microbiota composition or aberrant responses to luminal bacteria or dietary components can result in increased intestinal permeability, which may lead to the development of such pathologies. In this context, many studies have been conducted to investigate the therapeutic potential of certain commensal and probiotic strains to ameliorate inflammatory bowel diseases in clinical trials (reviewed by Chibbar and Dieleman, 2015; Wasilewski et al, 2015) or in animal models of colitis (Ewaschuk et al, 2008; Arribas et al, 2009; Shen et al, 2012; Kang et al, 2013; Martin et al, 2014; Souza et al, 2016). In mice colitis models, beneficial bacteria reduce inflammatory cytokines, normalize gut permeability, and reinforce the epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli Nissle 1917 (EcN) is a Gram-negative probiotic used to treat intestinal disorders, and particularly in maintaining remission of ulcerative colitis (Kruis et al, 2004; Chibbar and Dieleman, 2015). The strain, which was originally isolated from a soldier who survived a severe outbreak of diarrhea during the First World War, is a good colonizer of the human gut and positively affects gastrointestinal homeostasis and microbiota balance.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analyses of Sand et al [17], Chibbar and Dieleman [18] and Derikx et al [19] confirmed the opinion on positive effects of administration of probiotics and stressing importance of Bifidobacterium component of the administered probiotic preparations. It is of interest that probiotics application was related to an increase of Enterobacteriaceae in our patients with acute UC.…”
Section: Discussionmentioning
confidence: 82%
“…We have shown that, among others, the numbers of Bifidobacteria are low in children with early, acute UC [15]. Wang [16] concluded recently that Bifidobacteria and Lactobacilli are increased in patients with active IBD after application of probiotics.A recent meta-analyses of Sand et al [17], Chibbar and Dieleman [18] and Derikx et al [19] confirmed the opinion on positive effects of administration of probiotics and stressing importance of Bifidobacterium component of the administered probiotic preparations. It is of interest that probiotics application was related to an increase of Enterobacteriaceae in our patients with acute UC.…”
mentioning
confidence: 82%
“…We preferred cocktail VSL#3 as probiotic supplementation because VSL#3 is one of the most beneficial recommendations for ulcerative colitis therapy [23] and leads to a reduction in colonic expression of pro-inflammatory cytokines and mucosal damage and stimulates barrier integrity in different cases of colitis [24] or in common bile duct ligation induced inflammatory response [25] . We here show that 5-week moderate exercise and probiotic VSL#3 supplementation together led to reductions in some cytokine levels whereas only moderate exercise or probiotic VSL#3 supplementation does not, suggesting that usage ÜNSAL, ÜNSAL, ÜNER, KOÇ YILDIRIM EKİCİ, BALKAYA, BELGE of probiotic VSL#3 during moderate exercise improves immune system, at least in part with these experimental conditions.…”
Section: Discussionmentioning
confidence: 99%